KESULITAN PESERTA DIDIK DALAM BELAJAR FIQIH PADA MASA NEW NORMAL DI MTsN 1 LIMA PULUH KOTA - Iya Lovita (El-Rusyd, 2021)
This research is based on the phenomenon experienced by class VII students at MTsN 1 Lima Puluh Kota, because class VII students experience learning difficulties during the new normal period. Learning difficulties are a condition caused by obstacles and disturbances in learning. Starting during the Covid-19 period, students were told to study online, this is contained in a government regulation through the Ministry of Religion of the Republic of Indonesia, since mid-March 2020. During this new normal period, students must comply with regulations from the school because learning is online, face-to-face and blended. Learning. The problems faced by students in the new normal are influenced by several factors, namely internal factors and external factors.This study aims to reveal what are the difficulties of students learning fiqh in the new normal period at MTsN 1 Lima Puluh Kota. The research used is descriptive qualitative research, which is a complete and in-depth description of social reality and phenomena that occur in the community that is the subject of research. Methods of data collection using interviews and documentation. In conducting interviews using purposive sampling, namely the sampling technique with certain considerations. While the data analysis technique uses three stages, namely data reduction, data presentation and conclusion drawing.